Cell-extracellular matrix interactions can regulate the switch between growth and differentiation in rat hepatocytes: reciprocal expression of C/EBP alpha and immediate-early growth response transcription factors. - Rana, B (1994)
Previous investigations have shown that culture of freshly isolated hepatocytes under conventional conditions, i.e., on dried rat tail collagen in the presence of growth factors, facilitates cell growth but also causes an extensive down-regulation of most liver-specific functions. This dedifferentiation process can be prevented if the cells are cultured on a reconstituted basement membrane gel matrix derived from the Englebreth-Holm-Swarm mouse sarcoma tumor (EHS gel). To gain insight into the mechanisms regulating this response to extracellular matrix, we are analyzing the activities of two families of transcription factors, C/EBP and AP-1, which control the transcription of hepatic and growth-responsive genes, respectively. We demonstrate that isolation of hepatocytes from the normal quiescent rat liver by collagenase perfusion activates the immediate-early growth response program, as indicated by increased expression of c-jun, junB, c-fos, and c-myc mRNAs. Adhesion of these activated cells to dried rat tail collagen augments the elevated levels of these mRNAs for the initial 1 to 2 h postplating; junB and c-myc mRNA levels then drop steeply, with junB returning to normal quiescence and the c-myc level remaining slightly elevated during the 3-day culture period. Levels of c-jun mRNA and AP-1 DNA binding activity, however, remain elevated from the outset, while C/EBP alpha mRNA expression is down-regulated, resulting in a decrease in the steady-state levels of the 42- and 30-kDa C/EBP alpha polypeptides and C/EBP alpha DNA binding activity. In contrast, C/EBP beta mRNA production remains at near-normal hepatic levels for 5 to 8 days of culture, although its DNA binding activity decreases severalfold during this time. Adhesion of hepatocytes to the EHS gel for the same period of time dramatically alters this program: it arrests growth and inhibits AP-1 DNA binding activity and the expression of c-jun, junB, and c-myc mRNAs, but, in addition, it restores C/EBP alpha mRNA and protein as well as C/EBP alpha and C/EBP beta DNA binding activities to the abundant levels present in freshly isolated hepatocytes. These changes are not due merely to growth inhibition, because suppression of hepatocyte proliferation on collagen by epidermal growth factor starvation or addition of transforming growth factor beta does not inhibit AP-1 activity or restore C/EBP alpha DNA binding activity to normal hepatic levels. These data suggest that expression of the normal hepatic phenotype requires that hepatocytes exist in a G0 state of growth arrest, facilitated here by adhesion of cells to the EHS gel, in order to express high levels of hepatic transcription factors such as C/EBP alpha.